THE DEVELOPMENT OF MOBILE APPLICATION FOR DENGUE SITE INSPECTION IN JOHOR BAHRU - Noor Azmy, Suzanna; Huda Hashim, Nur Zarifah; Abd Wahid, Ainulbariah; Rizal Toha, Haidar (KURVATEK, 2023)
This study focuses on developing a user-friendly mobile application for dengue site inspection, aiming to address the persistent threat of vector-borne diseases in Malaysia. The current practice of dengue site inspection is still using paper-based method, which is inefficient, prompting the need for a mobile app solution. Existing methods for identifying and destroying breeding grounds, known as Destruction Action the Breeding Place (Pemusnahan Tempat Pembiakan, PTP), face constraints due to limited technology and information facilities. This leads to incomplete eradication and the need for repeated operations in the same areas, resulting increased in operational costs. To address these issues, a simple and user-friendly mobile application is designed to enhance field data entry, enable location tracking, and provide easy access to operational data from the inspection site. To reduce the effort on site record-keeping, the application is developed on the cost-effective open-source platform - QGIS, and QField. The aim is to improve the accuracy of PTP activities based on mobile application data and increase productivity through direct data entry in the field. The objectives of this study are to identify the requirements of a mobile application for dengue site inspection, develop a mobile application with location tracking enablement, and validate the results and effectiveness of the developed mobile application. The implemented apps were tested on the field by the health officer and 98% of them agree that the application does help the process of dengue site inspection and has significantly improved their workflow. The mobile application provided them with a user-friendly interface and streamlined data entry process, allowing them to easily capture and update information during dengue site inspections. The integration of location tracking capabilities also enabled them to accurately identify and record the precise coordinates of potential breeding sites. Overall, the positive feedback from the health officers demonstrates the effectiveness and usefulness of the developed application in enhancing the efficiency and effectiveness of dengue site inspections. The application aligns with the Sustainable Development Goal of Good Health and Well-Being and contributes to the digitalization process of the Fourth Industrial Revolution (Industry 4.0), aiming at reducing long-term operating costs.